PERAN ASEAN DALAM PENYELESAIAN SENGKETA KUIL PREAH VIHEAR - OKTAVINA YOHANA POTTU; CHONTINA SIAHAAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The study described asean’s role and step asa regional organization in resolving the conflict between Thailand and Cambodia on the border between the two countries in the temple preah vihear. Geographically the two countries bordered each country’s sovereign territory. This condition was a factor in border dispute between the countries. This border region has not escaped the arms conflict between Thailand and Cambodia. The research is aimed at knowing the role and policy of asean’s organisation as a third party in settling the conflict at the preah vihear temple. Using qualitative research methods, it deals with decryption methods and conflict resolution concepts in international relations. As a result of this study study, asean’s role in stabbing a race between Thailand and Cambodia.